Implementation of BERSABAR Method for Students to Achieve Clean and Healthy Schools in Al Ikhlas Private Elementary School Medan - Tumanggor, Winni R. E.; Chahaya, Indra; Siregar, Cholina Trisa (Talenta Publisher, 2023)
Sanitation conditions in the school environment in Urban Village Sitirejo II were not well managed. The school had adequate facilities, but these facilities were not optimally utilized as seen from the unavailability of clean water, unclean toilets, and scattered garbage. These conditions can lead to diseases such as diarrhea and others. The formation of cadres from students needs to be done to overcome these problems. The cadre was named Bocah Cinta Lingkungan or